Grazing reduces shrub-facilitated diversity of ground-dwelling arthropods in semiarid ecosystems - Jiancai Sun; Rentao Liu; Marcelo Sternberg; Lei Zhou; Zhimin Yang (Ecological Indicators)
It is well established that shrubs have facilitative effects on soil arthropods in semiarid ecosystems. However, there is limited knowledge about whether shrubs continue to exhibit these facilitative effects under grazing regimes. To investigate this, we examined the abundance, α and β diversity of ground-dwelling arthropods in microhabitats (shrub understory and open space) using pitfall trapping method in both ungrazed and grazed plots in a semiarid region of northwestern China. We also examined soil properties and plant attributes in order to explore the key drivers. Results indicated that there was no significant difference in abundance of ground-dwelling arthropods between both microhabitats in ungrazed plots, whereas it was significantly greater in shrub understory than in open space in grazed plots. There was significantly greater α and β diversity of ground-dwelling arthropods in shrub understory than in open spaces in ungrazed plots, whereas no significant difference in either index was observed between microhabitats in grazed plots. The decreased arthropod species turnover between microhabitats in grazed plots relative to ungrazed plots led to alterations of their original community assembly. The key drivers of herbaceous plant height in ungrazed plots and those of soil bulk density, soil organic carbon, and soil moisture in grazed plots shaped ground-dwelling arthropod distribution between microhabitats. In conclusion, grazing activities simplified the structure of ground-dwelling arthropod communities, resulting in lower α and β diversity in both shrub understory and open space in grazed plots compared to ungrazed plots.